PERii electronic journals: Assessing access and use by postgraduate students in the School of Education at the University of Dar es Salaam - Katabalwa, Anajoyce Samuel; Underwood, Peter G (University of Dar es Salaam Library Journal, 2017)
This paper is based on the findings of a study that assessed the awareness of Programme for Enhancement of Resources Initiative (PERii) electronic journals, their use and challenges encountered by postgraduate students. The study was carried out at the University of Dar es Salaam and involved postgraduate students in the School of Education. A combination of questionnaire for postgraduate students and interviews for Reference Librarians was used to collect data. Findings revealed that the majority of the respondents became aware of PERii electronic journals through various sources. The resources are widely used, including for the exploration of ongoing scientific debates through peer reviewed papers. The challenges encountered are largely infrastructural, including inability to access resources from home, together with limited information and computer literacy. Recommendations for improving access and use of PERii electronic journals are given.